ANALYSIS OF SERVICE QUALITY AT CEMPAKA PUTIH COMMUNITY HEALTH CENTER, CENTRAL JAKARTA - Julieta Maharani Dwiputri Marpaung; Retna Hanani (Journal of Management and Public Policy, 2026)
Health services are an important form of public service in improving the welfare of the community. Community health centers (Puskesmas) as primary health facilities are expected to be able to provide quality services to the community. This study aims to analyze the quality of services at the Cempaka Putih Community Health Center, Central Jakarta, based on the perceptions of the community. This study uses a quantitative approach with a survey method by distributing questionnaires to 88 respondents who are users of Puskesmas services. Service quality is measured using the five dimensions of SERVQUAL, namely tangibles, reliability, responsiveness, assurance, and empathy with the SERVPERF approach. The results show that the dimensions of assurance and empathy have a positive and significant effect on service quality. Meanwhile, the dimensions of tangibles, reliability, and responsiveness did not show a significant effect. This indicates that the competence of health workers, a sense of security, and the attention of staff are important factors in improving service quality at the Puskesmas.